Pemerolehan Bahasa Indonesia pada Anak Usia 5 – 6 Tahun: Studi Kasus Agata Astrid Sheila Simanihuruk - Simanihuruk, Agnes Monica; Rahayu, Ngudining; Supadi, Supadi (UNIB Press, 2025)
This study focuses on a case study of Agata Astrid Sheila Simanihuruk in the process of language acquisition of children aged five – six years. Language in children aged five – six years in particular has acquired a lot of vocabulary used to communicate with each other. This case study research aims to describe and analyze the types of words and types of sentences spoken by Agata who is the subject of this study. The research method used in this study is a qualitative descriptive method. Data collection in this study was by observing, recording and interviewing several members of Agata’s family. In each type of word and type of sentence obtained by Agata comes from Agata’s daily activities and habits, such as playing, watching TV, watching YouTube and interacting with family members and other people Agata meets. The results of this study show that in the acquisition of word types based on Kridalaksana, the verbs obtained by Agata are such as eating, playing and praying. Adjectives such us delicious, fast, nouns such as Dudung, slime, and Pak Somad. Pronouns such as the word aye, numerals obtained by Agata are the numbers one, two, three, four five. As for adverbs, it refers to Agata’s habit of answering such as already, yet. The interrogratives used by Agata are most dominantly the words what and who. One of the prepositions obtained by Agata is the word for, the most dominant conjunction uttered by Agata is the word and and in the phatic category, the most dominant one uttered by Agata is the word selamat which Agata gave when playing. So the type of word that Agata obtains the most is nouns and the type of word that Agata obtains the least is demonstrative. While the types of sentences focus on clause sentences, non-clause sentences, declarative sentences, interrogative sentences and imperative sentences which are also based on Agata’s daily activities in Agata’s enviroment. Agata, who is the subject of this case study research, acquires Indonesian as her first language naturally by imitating every activity and habit of Agata at home.